Ensiklopedia mini Anne Civardi, Ruth Thomson ; alih bahasa, Ratna Widawati ; editor, Tri Bharata, Margaretha Hutauruk Eddy, Rara Tanjung Hidayat - CIVARDI, Anne; Thomson, Ruth; Widawati,Ratna; Tri Bharata; Eddy, Margaretha Hutauruk; Hidayat, Rara Tanjung (2003)
160 hlm ilus 22 cm